Why is “It” Gendered – Constructing Gender in Alex Garland’s Ex-Machina (2015) - MUSAP, Emilia (Anafora, 2023)
Through the analysis of Alex Garland’s movie Ex-Machina (2015), the paper questions the cyborg’s possibility of representing a gender beyond the body and of embodying an entity beyond the human. Drawing inspiration from Donna Haraway, Judith Butler, and Roger Andre Sørra, this paper wants to position the cyborg’s body as an object of manipulation and control, as well as question the following resumptions: primarily, that the body of the cyborg is always gendered, despite the many technological possibilities of its (re)construction, and secondarily, that male and female cyborgs share a completely different storyline where the latter are positioned almost exclusively as sexual objects and/or love interests, and are coded as heterosexual. Accordingly, the aim of this paper is to illustrate how, instead of offering a progressive take on gender, Ex-Machina reinforces stereotypes by positioning gender as an instrument of male control, be it for the purpose of achieving the illusion of the human, for sexual gratification, or for the simple pleasure of asserting dominance.